STUDI PEMANFAATAN EKSTRAK BUAH NAGA DAGING MERAH (hylocereus polyhizus) SEBAGAI PEREDUKSI ION LOGAM Fe (III) - Muhammad Jumaing; Alimuddin Alimuddin (PROSIDING SEMINAR KIMIA, 2017)
A research about the utilization of red dragon fruit extract (Hylocereus polyhizus) as reducer of Fe (III) metal ions has been done. This research aims to determine the optimum condition of reducer solution of dragon fruit extract to reduce Fe (III) metal ions based on variation of Fe solution concentration and also ph variation with Na2S2O3 reductant as comparison. The results showed that the optimum concentration of the dragon fruit extract reducer agent could reduce Fe (III) metal ion to Fe (II) at a concentration of 10 mg / L, Fe reduced as much as 1.187 mg / L, while the optimum pH is at pH 5 when Fe reduced of 1.436 mg / L. The concentration of Na2S2O3 reducant was at concentrations of Fe 10 mg / L with reduced Fe of 0.538 mg / L while the optimum pH was at pH 5 with a reduced Fe of 0.511 mg / L. From the results of this research with both reducers it can be seen that the dragon fruit extract reduces Fe metal ion better than the reduction of Na2S2O3. Keywords: Fe metal ion, reductant, dragon fruit extract (Hylocereus polyhizus), Na2S2O3, determination of % Fe is reduced, optimum pH.